2020
DOI: 10.1016/j.xnsj.2020.100036
|View full text |Cite
|
Sign up to set email alerts
|

Septic cavernous sinus thrombosis secondary to halo vest pin site infection

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Rahimizadeh et al reported a case of septic CST secondary to a halo pin-site infection. In this case, CST occurred because of unrecognized pin-site infection and presented with proptosis and ipsilateral eyelid edema; however, with early consideration of CST and aggressive antibiotic and anticoagulant therapy, the patient had a favorable outcome [37][38][39][40][41][42][43][44].…”
Section: Infectious Cavernous Sinus Thrombosis: Infectiousmentioning
confidence: 89%
“…Rahimizadeh et al reported a case of septic CST secondary to a halo pin-site infection. In this case, CST occurred because of unrecognized pin-site infection and presented with proptosis and ipsilateral eyelid edema; however, with early consideration of CST and aggressive antibiotic and anticoagulant therapy, the patient had a favorable outcome [37][38][39][40][41][42][43][44].…”
Section: Infectious Cavernous Sinus Thrombosis: Infectiousmentioning
confidence: 89%